Family-Friendly Tax Preferences and Child Benefits in the Federal Republic of Germany - Franielczyk, Anna (Journal of Finance and Financial Law, 2017)
In contemporary economies an important part in tax revenue system is frequently played by preferences associated with expending a gained income. Particularly essential in this matter are exemptions and tax advantages which cause tax base reduction or tax payable reduction. The most common among tax preferences is dependency exemption for those who have or raise child/children. Tax deductions have got a positive impact on household budget as they reduce tax payable and are an additional household financial source. In this paper we aim at analysing family-friendly tax deductions and preferences as well as family allowance in the Federal Republic of Germany and determining their influence on state budget.